ACTION Malaysia—perception and barriers to obesity management among people with obesity and healthcare professionals in Malaysia - Nor Hanipah, Zubaidah; Abdul Ghani, Rohana; Mohd Efendy Goon, Mohd Danial (BioMed Central, 2025)
Background: Timely weight loss conversations between healthcare professionals (HCPs) and people with obesity (PwO) can help in effective obesity management. The Awareness, Care, and Treatment in Obesity maNagement in the Asia Pacific region (ACTION APAC) studied the attitudes, perceptions, and behaviours toward obesity among PwO and HCPs in nine countries of South and Southeast Asia. The current study is a subgroup analysis based on the Malaysian population, known as ACTION Malaysia (ACTION-MY), and aims to explore the attitudes, perceptions, behaviours, and barriers to effective obesity management among both PwO and HCPs. Methodology: An online survey in dual languages (Malay and English) was conducted between April 2022 and May 2022 among 1001 adult PwO and 200 HCPs (general practitioners, endocrinologists, obstetricians/gynaecologists, cardiologists, and other appropriate specialities). Results: The findings highlighted significant gaps in obesity awareness, with 57% of PwO misclassifying their weight status as normal or overweight. While 68% of PwO valued discussing weight management with HCPs, success rates remained low. On average, patients made three weight loss attempts in adulthood, with 63% regaining weight even after maintaining weight loss for six months or more. Key barriers included insufficient exercise, motivation deficits, and poor hunger control. Although 88% of HCPs recognised obesity as a chronic disease affecting overall health, patient disinterest, limited awareness of treatment options, and time constraints hindered effective intervention. Despite 70% of PwO trusting HCPs’ medication recommendations, only 10% received weight loss prescriptions. Conclusions: This study emphasises the need for enhanced communication between HCPs and PwO, along with comprehensive support that includes mental health services. Addressing the perception gap regarding weight management responsibility is crucial. The results suggest that culturally contextualised approaches to obesity management in Malaysia are essential. Our findings highlight the urgent need for developing treatment strategies and policies targeting identified barriers and establishing collaborative frameworks to enhance obesity management within Malaysia’s healthcare system.